1990
DOI: 10.1063/1.345390
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state thin-film memistor for electronic neural networks

Abstract: We report on a tungsten-oxide-based, nonvolatile, electrically reprogrammable, variable resistance device as an analog synaptic memory connection for electronic neural networks. A voltage controlled, reversible injection of H+ ions in electrochromic thin films of WO3 is utilized to modulate its resistance. A hygroscopic thin film of Cr2 O3 is the source of H+ ions. The resistance of the device can be tailored and stabilized over a wide dynamic range (∼four orders of magnitude), and the programming speed is mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 6 publications
0
56
0
1
Order By: Relevance
“…After 30 s proton injection at 200°C, the channel resistivity increases from o1 to B2 Â 10 3 mO cm. It is found that a large amount of hydrogen gas pockets develop cumulatively during the anodic reaction of SNO under negative gating, which eventually leads to the rupturing of Pd layer 30 . Overloaded protons facilitate this blistering process and underloading helps to prolong the lifetime of the Pd electrode.…”
Section: Doping-induced Phase Transition By LI and Mg Intercalationmentioning
confidence: 99%
“…After 30 s proton injection at 200°C, the channel resistivity increases from o1 to B2 Â 10 3 mO cm. It is found that a large amount of hydrogen gas pockets develop cumulatively during the anodic reaction of SNO under negative gating, which eventually leads to the rupturing of Pd layer 30 . Overloaded protons facilitate this blistering process and underloading helps to prolong the lifetime of the Pd electrode.…”
Section: Doping-induced Phase Transition By LI and Mg Intercalationmentioning
confidence: 99%
“…Current two-terminal metal-insulator-metal artificial synapses operate by separating the signal transmission and selflearning processes in time 8,9 . Three-terminal synaptic devices, being able to realize both functions simultaneously, therefore offer a promising solution for efficient synapse simulation [23][24][25][26][27][28] .…”
mentioning
confidence: 99%
“…Hence, the memristor research did not lead to the development of any major hardware types, except for a few notable projects in the 1990s 14,15 . However, the situation has changed dramatically in recent years 8 , and memristor technology is rapidly advancing owing to the large-scale semiconductor industry's effort to develop digital memristor-based crossbar memories.…”
mentioning
confidence: 99%